Protocol for assessing the determinants of preoperative test-ordering behaviour for low-risk surgical procedures using a theoretically driven, qualitative design. Issue 5 (11th May 2020) - Pike, Andrea; Mahoney, Krista; Patey, Andrea M; Inwood, Samantha; Mortazhejri, Sameh; Lawrence, Rebecca; Hall, Amanda
Abstract : Introduction: Current evidence suggests that preoperative tests such as chest X-rays, electrocardiograms and baseline laboratory studies may not be useful for healthy patients undergoing low-risk surgical procedures. Routine preoperative testing for healthy patients having low-risk surgery is not a scientifically sound practice. In this study, we will interview healthcare providers working at medical facilities where low-risk surgical procedures are carried out. This will allow us to gain insight into the determinants of preoperative testing behaviours for healthy patients undergoing low-risk surgeries and their barriers and enablers to guideline adherence. Methods and analysis: We will use semistructured interviews with anaesthesiologists, surgeons and preadmission clinic nurses to assess the determinants of preoperative testing behaviours. The interview guide was designed around the Theoretical Domains Framework (TDF), developed specifically to determine the barriers and enablers to implementing evidence-based guidelines. Interviews will be audio-recorded, transcribed verbatim and coded according to the TDF. Key themes will be generated for each of the identified domains. Ethics and dissemination: We have received ethics approval from the Health Research Ethics Board in Newfoundland and Labrador (HREB #2018.190) for this study. The results of this work will be disseminated through a peer-reviewed publication, presentation at a healthcare forum and plain-language infographic summaries. Additionally, deidentified data collected and analysed for this study will be available for review from the corresponding author on reasonable request.